STUDI INTERPRETATIF TERHADAP MAKNA DAN NILAI PENDIDIKAN DALAM LAGU SAYANG API COA SAYANG DARI REJANG LEBONG - Silvi Ulandari; Robby Ferdian (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to uncover the meaning and educational values of the Rejang Lebong folk song